Resource distribution, growth and strategies for enhancing fish production in north-eastern states of India - DebRoy, Piyashi; Krishnan, M.; D. Upadhyay, Anil; Ramasubramanian, V.; R. Criddle, Keith; Kiresur, V. R.; K. Datta, Samar (Indian Journal of Fisheries, 2016)
Contribution of the eight north-eastern states of India towards national fish production is only 5.9% despite the vast resources available in the region. There is a clear disparity in the total fish production vis-a-vis the potential in these states of India. This paper estimates the growth and instability of fish production in the north-eastern states of India relating the performance to the resource availability in the region and suggests strategies for enhanced fish production. Compound growth rates and Coppock’s instability index were used to determine the growth and performance of fish production in these states. Assam emerged as the state producing the maximum quantity of fish among the eight north-eastern states during the period 1999-2010. The share of Tripura was 16% and only 13% of the total fish production was contributed by the other six states. In terms of productivity, Manipur followed by Tripura and Mizoram head the table. There is considerable scope for improving the performance of fisheries sector in the north-eastern states of India by adoption of appropriate technologies and up-scalable models.